Integrating cardiac MRI into pre-operative planning for patients with pectus excavatum and right ventricular dysfunction - Krista Lai; Timothy M. Colen; Bryan J. Dicken (Elsevier, 2019)
A 16-year old male presented with severe pectus excavatum (PE) with a Haller index of 3.4. The patient was a physically fit individual, with no identifiable limitation in his daily activities. However, despite his level of fitness, he experienced significant and reproducible exercise limitation at peak exertion. The patient was evaluated with a static echocardiogram that showed a normal right ventricle (RV), with reduced systolic function-RV fractional area change (FAC) measuring 20% (normal >35%). A pre-operative cardiac MRI confirmed reduced RV function (RV ejection fraction (EF) 35% - normal >50%), dilated RV, and reduced left ventricular (LV) function (LV EF 43% - normal >55%). He proceeded with a Nuss bar repair. Post-operative echocardiogram revealed improved RV function with RV FAC greater than 35%. We show that in patients with PE and minimal symptoms at rest, cardiac MRI may reveal additional functional information in addition to echocardiography, to explain exertional symptoms. We also demonstrate resolution of cardiac dysfunction with surgical repair of PE. Keywords: Pectus excavatum, Cardiac dysfunction, MRI